Core Binding Factor β Plays a Critical Role During Chondrocyte Differentiation. Issue 1 (January 2016) - Park, Na‐Rae; Lim, Kyung‐Eun; Han, Min‐Su; Che, Xiangguo; Park, Clara Yongjoo; Kim, Jung‐Eun; Taniuchi, Ichiro; Bae, Suk‐Chul; Choi, Je‐Yong
<x xml:space="preserve">Abstract</x> Core binding factor β (Cbfβ) is a partner protein of Runx family transcription factors with minimally characterized function in cartilage. Here we address the role of Cbfβ in cartilage by generating chondrocyte‐specific Cbfβ‐deficient mice (CbfbΔch/Δch) from Cbfb‐floxed mice crossed with mice expressing Cre from the Col2a1 promoter. CbfbΔch/Δch mice died soon after birth and exhibited delayed endochondral bone formation, shorter appendicular skeleton length with increased proliferative chondrocytes, and nearly absent hypertrophic chondrocyte zones. Immunohistochemical and quantitative real‐time PCR analyses showed that the number and size of proliferative chondrocytes increased and the expression of chondrocyte maturation markers at the growth plates, including Runx2, osterix, and osteopontin, significantly diminished in CbfbΔch/Δch mice compared to wild type mice. With regard to signaling pathways, both PTHrP‐Ihh and BMP signaling were compromised in CbfbΔch/Δch mice. Mechanistically, Cbfβ deficiency in chondrocytes caused a decrease of protein levels of Runx transcription factors by accelerating polyubiquitination‐mediated proteosomal degradation in vitro. Indeed, Runx2 and Runx3, but not Runx1, decreased in CbfbΔch/Δch mice. Collectively, these findings indicate that Cbfβ plays a critical role for chondrocyte differentiation through stabilizing Runx2 and Runx3 proteins in cartilage J. Cell. Physiol. 230: 162–171, 2016. © 2015 Wiley Periodicals, Inc.